Skeletal changes following surgically assisted rapid maxillary expansion (SARME) - İpek Kaçar; Çağrı Deli̇lbaşı; Nevin Kaptan Akar; Gökhan Gürler (Istanbul University, 2018)
DOI: 10.26650/eor.2018.465Purpose Surgically assisted rapid maxillary expansion (SARME) is a common treatment technique in the correction of maxillary transverse deficiency. The purpose of this study was to evaluate nasal and palatal skeletal changes following SARME using Cone Beam Computed Tomography (CBCT) and posterior anterior (PA) cephalograms. Materials and Methods In this retrospective study, the radiographic images obtained from 14 patients with transverse maxillary deficiency before treatment and 6 months after SARME operations were evaluated. The changes in nasal bone width and palatal bone width were measured on CBCT. The changes in basal maxillary width, nasal cavity width and angular measurements were evaluated on PA cephalograms. Results Nasal floor width was measured at the levels of upper first premolar teeth and molar teeth which significantly increased following SARME (p=0.005 and 0.017 respectively). Palatal bone width between first premolar teeth and molar teeth also significantly increased (p=0.003 and 0.002 respectively). Basal maxillary width (p=0.026), nasal cavity width (p=0.024) and other angular measurements also significantly increased (p<0.05). Conclusion Nasal and palatal skeletal transverse dimensions increased following SARME. Due to the enlargement of the nasal floor and nasal cavity, it is likely to improve air pass through the nose.